Protection of corneal endothelium from apoptosis by gene and cell therapy - Fuchsluger, Thomas (Ophthalmologe, 2016)
Protection of corneal endothelium from apoptosis using gene and cell therapy is in a translational phase. This approach offers advantages for eye banking and after transplantation. Safe vehicles for gene or cell therapeutic transduction of corneal endothelium with nucleic acids are available. This strategy will be further developed in consultation with the Paul Ehrlich Institute and European regulatory authorities.
EVALuna2:21284